Road development, economic growth, and poverty reduction in China - Fan, Shenggen; Chan-Kang, Connie (International Food Policy Research Institute, 2005)
Since 1985, the Chinese government has given high priority to building roads, particularly high-quality roads that connect industrial centers. This report evaluates the contribution roads have made to poverty reduction and economic growth in China over the last two decades. It disaggregates road infrastructure into different classes to account for differences in their quality, and then estimates the impact of road investments on overall economic growth, agricultural growth, urban growth, urban poverty reduction, and rural poverty reduction. The report makes the case for a greater focus on low-quality and rural roads in future infrastructure investment strategies in China. It does so by showing how investing in low-quality and rural roads will generate larger marginal returns, raise more people out of poverty per yuan invested, and reduce regional development disparity more sharply than investing in high-quality roads. The study’s findings will have considerable implications for China’s infrastructure policy.